The Preterm Gut Microbiota: An Inconspicuous Challenge in Nutritional Neonatal Care - Henderickx, Jannie G. E.; Zwittink, Romy D.; van Lingen, Richard A.; Knol, Jan; Belzer, Clara (Frontiers in Cellular and Infection Microbiology, 2019)
The nutritional requirements of preterm infants are unique and challenging to meet in neonatal care, yet crucial for their growth, development and health. Normally, the gut microbiota has distinct metabolic capacities, making their role in metabolism of dietary components indispensable. In preterm infants, variation in microbiota composition is introduced while facing a unique set of environmental conditions. However, the effect of such variation on the microbiota’s metabolic capacity and on the preterm infant’s growth and development remains unresolved. In this review, we will provide a holistic overview on development of the preterm gut microbiota and the unique environmental conditions contributing to this, in addition to maturation of the gastrointestinal tract and immune system in preterm infants. The role of prematurity, as well as the role of human milk, in the developmental processes is emphasized. Current research stresses the early life gut microbiota as cornerstone for simultaneous development of the gastrointestinal tract and immune system. Besides that, literature provides clues that prematurity affects growth and development. As such, this review is concluded with our hypothesis that prematurity of the gut microbiota may be a clinical challenge in achieving optimal feeding besides traditional challenges such as preterm breast milk composition, high nutritional requirements and immaturity of the gastrointestinal tract and immune system. A better understanding of the metabolic capacity of the gut microbiota and its impact on gut and immune maturation in preterm infants could complement current feeding regimens in future neonatal care and thereby facilitate growth, development and health in preterm infants.